How do wise leaders perform? Conceptualizing wise leadership and its styles - Dashtaki, Arezoo Soleimani; Eskandari, Hossein; Borjali, Ahmad; Oreyzi, HamidReza; Sternberg, Robert J. (Zielona Góra: Faculty of Economics and Management Press)
Wisdom is proposed as a bridge between leader and leadership. It is necessary to explore what characteristics wise leaders have and what approaches they use to solve problems. In this study, we suggest a unique approach involving qualitative and quantitative research methods to seek the essence of wise leadership and its styles. The research employed Cognitive Task Analysis (CTA) to conduct interviews with nine wise leaders in management positions.
Keywords: Wisdom; transactional wise leadership; transformational wise leadership; leadership style; ethical leadership